Euler deconvolution of satellite gravity and magnetic data for the area around the Río de la Plata. (November 2022) - Baxter, Peter
Abstract: Prior investigations have suggested that there may be greater seismic hazard to Buenos Aires and Montevideo than is currently allowed for in design codes and regulations. Analyses of risk have, however, been hampered by lack of knowledge concerning potentially seismogenic faults under the Río de la Plata estuary and the adjacent area of Buenos Aires Province south of the estuary. This work uses satellite gravity anomaly and magnetic intensity data, together with Euler deconvolution, to find lineations in the perturbations of these fields that may be indicative of buried geological features such as faults, dykes, boundaries etc. These lineations were then compared with faulting documented in the literature, which showed reasonable correlation. However, the results also suggested a number of lineations of significant length that have not been documented to date. These lineations are discussed in terms of the limits of prior investigations, and the possibility of their being indicative of potentially seismogenic faulting, of sufficient size to cause significant hazard to the 18 million citizens of Uruguay and Argentina living close to the Río de la Plata. It is proposed that this work shows the feasibility of using this approach, and that with the availability of more complete data sets and more sophisticated software, further investigation will be enabled. Highlights: Euler deconvolution of satellite gravity and magnetic field data. Determination of lineaments exceeding 50 km in length around Rio de la Plata. Validation against documented faulting. Identification of significant lineaments not documented to date.